Pengaruh Norma Subjektif dan Persepsi Manfaat Terhadap Intensitas Menggunakan Fintech Payment dengan Sikap Pengguna Sebagai Variabel Intervening (Studi Kasus: Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Sumatera Utara) - Tanzila Arifah Putri; Nurbaiti Nurbaiti; Juliana Nasution (Universitas Labuhanbatu, 2023)
This study aims to analyze the effect of subjective norms and perceptions of benefits on the intensity of using fintech payment intervened through user attitude variables. The type of research used that is used is quantitative research with causality research design.The population in this study amounted to 3973 respondents.By using non-probability sampling sampling technique, a sample of 98 people was taken using slovin formula.The data analysis technique used is path analysis. The results showed that partially subjective norm variables had no significant effect on the intensity of using fintech payment, but the perception of benefits and user attitudes had a significant effect on the intensity of using fintech payment. Subjective norm variables affect user attitudes, while the perception of benefits does not affect user attitudes. When intervened with user attitude variables, subjective norm variables affect the decision intensity of using fintech payment. While the perception of benefits does not affect the intensity of using fintech payment.As well as subjective norms, perceptions of benefits and user attitudes simultaneously affect the intensity of using fintech payments.